2020
DOI: 10.1155/2020/1134744
|View full text |Cite
|
Sign up to set email alerts
|

Does Anemia Have a Potential Effect on Type 2 Hepatorenal Syndrome?

Abstract: Background/Aims. Hepatorenal syndrome (HRS) is a form of functional renal failure arising in advanced cirrhosis and is characterized by a poor survival rate. Anemia is frequently observed during the clinical course of cirrhosis. Our study aimed to investigate the hematologic findings in patients with cirrhosis to determine the effects of anemia on renal functions in type 2 HRS and if it was a potential aggravating factor. Materials and Methods. This prospective study, in which all consecutive patients with cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Hemolytic anemia is reported to complicate 1-14% of cases of advanced liver disease, 1,4 but in some clinical entities can be much more prevalent. Cases of immune-mediated hemolytic anemia can complicate autoimmune liver diseases, such as autoimmune hepatitis, PBC and PSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolytic anemia is reported to complicate 1-14% of cases of advanced liver disease, 1,4 but in some clinical entities can be much more prevalent. Cases of immune-mediated hemolytic anemia can complicate autoimmune liver diseases, such as autoimmune hepatitis, PBC and PSC.…”
Section: Discussionmentioning
confidence: 99%
“…They also more frequently develop complications of cirrhosis such as type 2 hepatorenal syndrome, and supposedly gastrointestinal bleeding and ascites. 1,2 Anemia prevalence in hepatology is associated with the degree of impairment of liver function and portal hypertension. Prevalence of anemia is especially high in the context of liver cirrhosis, where decreased concentration of hemoglobin is reported to affect around 70% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia can reduce the oxygen supply of the kidney and may lead to microcirculation renal hypoxia or injury, which can cause early renal tubular injury [18,19] , and renal ischemia is the most common cause of HRS. Studies have found that anemia can aggravate HRS in patients with liver cirrhosis [20] . In patients with end-stage renal disease, there was a strong positive correlation between anemia and risk of adverse prognosis [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia is known to increase local inflammation in the kidney[ 77 ]. Studies assessing the relationship between anemia and HRS development have found low serum hemoglobin to be associated with HRS type 2[ 78 ]. As anemia is more common and is more pronounced in males with CLD[ 79 ], it is possible that hypoxia related inflammation predisposes males to the more profound inflammatory response in HRS-AKI.…”
Section: Pathophysiologymentioning
confidence: 99%